A fluorescent probe with aggregation-induced emission characteristics for distinguishing homocysteine over cysteine and glutathione1. Issue 32 (28th August 2015) - Zhao, Na; Gong, Qian; Zhang, Rui Xue; Yang, Jun; Huang, Zhi Yan; Li, Nan; Tang, Ben Zhong
<x xml:space="preserve">Abstract</x> In this work, a novel AIE fluorescent probe, TPE-Py, containing an α, β-unsaturated ketone unit was developed for discriminating homocysteine over cysteine and glutathione.